ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN PEMERINTAH DAERAH - Abdul Rohman; Rochmawati Daud; Ubaidillah Ubaidillah (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
Our study wants to test whether opinions, accrual levels, and accruals are influential or not on the financial performance of local governments. the use of accrual accretion using the five Healy model, Angelo, Hribar, Jones, and modification is expected to capture more thoroughly each local government management policy related to financial management accrual discretion and the preparation of local government financial reports. The results of processing data show that the first model (Healy, Angelo, Jones, and Modification) shows results that reject the alternative hypothesis. The third research model, Hribar, showed positive results, namely accepting alternative hypotheses. We use the SPSS statistical tool to carry out multiple regression testing. The first hypothesis shows a negative result so that it is rejected ie opinion does not affect financial performance. The second hypothesis, the level of accruals influences financial performance is rejected. While accruals (H3) are accepted. And together these three variables have a weak influence on the financial performance of local governments. The hribar model accruals discretion shows the existence of factors that influence financial performance derived from several factors. Hribar accrual formulation is influenced by two factors, namely cash flow and budget realization (deficit). Thus the authors conclude that the accrual policy in the financial statements of local governments is influenced by surplus (deficit budget realization) and local government cash flows. Opinion and accrual levels do not affect the government's financial performance.